Influence of The Dietary Thermo-Mechanically Fermented Soybean Meal on Chicken Meat Quality of Jawa Super Male Chicken - Saputro, Wahyu Subagio; Muhammad Arif Darmawan; Pramita Nindya Saraswati; Aan Andri Yano; Novi Akhirini; Wahyu Setyono; Wara Pratitis Sabar Suprayogi (ANIMAL PRODUCTION, 2024)
The meat quality of Jawa Super Male Chicken is attributed to the diet treatment offered since the rearing period. This study aimed to evaluate the meat quality of Jawa Super Male Chickens fed on diets made of soybean meal (SBM) fermented with Bacillus subtilis or Aspergillus niger. The experimental groups were control group without steam conditioning or fermentation (P0), SBM fermented with Bacillus subtilis or SBM BS (P1), and SBM fermented with Aspergillus niger or SBM ASP (P2). Ninety chickens aged 21 days (210 ± 3.69 grams) were assigned to three groups, and replicated six times with five birds. Basal diets were made of corn-soybean with 16% crude protein (CP) and 2,950 Kcal metabolic energy (ME). The results showed significant differences (P<0.05) in the physical attributes (cooking loss, water holding capacity) and chemical properties (fat content) but the collagen and protein content did not differ significantly (P>0.05). The meat pH was within the normal range of 5.90 – 5.93. Conclusively, SBM fermented with Bacillus subtilisor Aspergillus niger increased meat quality.